PERENCANAAN PENDIDIKAN UNTUK MENINGKATKAN KOMPETENSI GURU DI MADRASAH ALIYAH SWASTA AL-JAMI’ATUL ALWASHLIYAH 22 TEMBUNG - Rizki Akmalia; Inda Lestari; Fatimah Azzahra; Syarifah Tussuriyani Hasibuan; Ahmad Fauzan Nafis (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
This research aims to analyze in depth educational planning to improve teacher competency at MAS Al-Jami'atul Washliyah 22 Tembung. Educational planning to improve teacher competency is one of the key factors in creating quality resources in an educational institution, which can improve teacher performance and productivity. This research uses qualitative case study methods, which allows in-depth analysis of the dynamics of educational planning to improve teacher competence. The research data was obtained based on observations and answers to questions that the author asked to parties involved in the direct interview process in the field, with the respondent being a deputy head of the madrasah. Apart from that, analysis of documents related to educational planning to improve teacher competence was also carried out to obtain a more comprehensive picture. The research results show that good planning in improving teacher competency in a madarsah has a great influence on improving human resources for educators, especially teachers.